Waste of space - Damico, Gina (Houghton Mifflin Harcourt, 2017)
"Cram ten hormonal teens into a spaceship and blast off: that's the premise for the ill-conceived reality show Waste of Space. The kids who are cast know everything about drama--and nothing about the fact that the production is fake"--